The Impact of Consumption Patterns and Urbanization on the Cross-Regional Water Footprint in China: A Decomposition Analysis - Liu, Hui; Wei, Liyuan; Chen, Chang; Wang, Zhen (Frontiers in Environmental Science, 2022)
The increasingly urbanized population and corresponding consumption changes are causing the household water footprint to rise. However, the quantity of these changes remains to be determined. Here, we combine a two-stage factor reversible structural decomposition analysis with multi-regional input-output analysis to explore the hidden driving forces of the changes in the household water footprint and the impacts of urbanization and consumption patterns on the cross-regional water footprint from 2012 to 2017. The results show that the national household water footprint dropped from 292.33 billion m3 to 291.18 billion m3 and exhibited a decreasing trend in the east and an increasing trend in the west; the driving factors were classified and ranked as technological level (-75.6 billion m3), consumption patterns (52.6 billion m3) and population (21.8 billion m3). Among all driving factors, both urbanization and the associated consumption pattern transformation caused an increase in the cross-regional water footprint, except in several developed provinces, such as Shanghai and Guangdong, which suggested that decoupling might exist between economic development and the water footprint. Overall, heterogeneous policies were suggested to be made according to local water resource endowments and their positions in the production chain. Our results clarify the effects of different socio-economic factors on the cross-regional water footprint during the process of urbanization and provide refined insights for future water conservation.